QuizCorrect answer to the quiz. check your diagnosisOncogenic osteomalacia associated with phosphaturic mesenchymal tumour, mixed connective tissue type of the knee - Szumera-Ciećkiewicz, Anna; Ptaszyński, Konrad; Pawełas, Andrzej; Rutkowski, Piotr (Polish Journal of Pathology, 2009)
One of the most unusual and uncommon types of osteomalacia is the oncogenic osteomalacia that is predominantly caused by a soft tissue or bone tumour, mostly by a phosphaturic mesenchymal tumour, mixed connective tissue type (PMTMCT). We report a case of a 27-year-old male presented with complaints of progressive and generalized muscle weakness, bone pains and multiple fractures. Intra-articular PMTMCT of the knee was diagnosed and surgically removed. We describe histopathological features of PMTMCT and review the most recent studies concerning this diagnostic problem.